Profile of notification sexual violence against boys, sinan 2009-2017, Brazil (Research, Society and Development, 2021)
This study analyzed the epidemiological profile of notification of sexual violence against male children in Brazil, based on the Sistema de Informação de Agravos de Notificação (SINAN), between 2009 and 2017.All notifications of sexual violence against boys were considered according with the variables age, skin color, place of occurrence, relationship with the victim and recurrence. Data were extracted and presented in tables as absolute frequency and percentage. During the analyzed period, there were 17,451 reports of sexual violence against boys. The number of notifications increased by almost 3.5 times, from 790 in 2009 to 2,750 in 2017. The 5-9 years age group had the highest number of notifications (10,836 cases), and the highest prevalence of notifications was in the Southeast region (42.5%). The information produced in this study may be useful for planning actions or public policies aimed at male children victims of sexual violence.